1983
DOI: 10.1111/j.1471-0528.1983.tb08923.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of liver protein induction in postmenopausal women during oral and percutaneous oestrogen replacement therapy

Abstract: Two groups of postmenopausal women with climacteric symptoms were investigated during unopposed cyclic replacement therapy with tablets of micronized 17P-oestradiol (2 mg daily) and percutaneous 17P-oestradiol (3 mg daily). The resultant serum levels of 17P-oestradio1, total oestrone and three liver proteins: sex-hormone-binding globulin (SHBG), pregnancy-zone protein (PZP) and caeruloplasmin were followed. In both groups similar levels of serum 17P-oestradiol (ca 500 PM) were recorded, while the increase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 26 publications
1
20
1
1
Order By: Relevance
“…Recent studies using non-orally administered estrogens have shown a smaller incidence of these side effects, thus confirming the importance of avoiding supraphysiological hepatic concentrations of this steroid, particularly in patients who are hypertensive or at the risk of suffering thromboembolism (19,20). In the present study we observed that, during the hormone treatment, the plasma levels of liver proteins considered to be specific markers of estrogen action (PRA, A-III, lipids, and lipoproteins) remained stable, showing that the percutaneous administration of the drug did not alter the estrogen-dependent hepatic metabolism.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recent studies using non-orally administered estrogens have shown a smaller incidence of these side effects, thus confirming the importance of avoiding supraphysiological hepatic concentrations of this steroid, particularly in patients who are hypertensive or at the risk of suffering thromboembolism (19,20). In the present study we observed that, during the hormone treatment, the plasma levels of liver proteins considered to be specific markers of estrogen action (PRA, A-III, lipids, and lipoproteins) remained stable, showing that the percutaneous administration of the drug did not alter the estrogen-dependent hepatic metabolism.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, it is known that the high initial levels of estrogen in the liver following oral administration may cause considerable changes in hepatic metabolism. Many of the negative side effects of estrogen replacement therapy derive from changes in the synthesis of liver proteins that result from first-passage metabolism (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of oestrogen causes a rapid increase in the plasma level of PZP, whereas percutaneous administration of the same steroid, resulting in equally high concentrations of circulating oestrogen caused no change in the PZP level (Holst et al, 1983). During pregnancy there is no apparent correlation between the concentration of oestrogens and PZP , and there is no significant variation of PZP during the menstrual cycle and concentrations are not, affected by the menopause (Damber et al, 1976;Folkersen et al, 1981).…”
Section: Abstract: Pregnancy-associated Murine Protein-i; Snell Dwarfmentioning
confidence: 99%
“…This effect has been related to alterations in the serum lipoprotein profile and especially to the increased concentrations of high-density lipoprotein (HDL) cholesterol during therapy [1,2], The route of adminis tration is important in this respect since oral estrogen therapy will increase the serum con-centration of several estrogen-sensitive liver proteins, including HDL subfractions in a dose-dependent manner, while there is no such effect when equipotcnt amounts of estro gen are given parenterally [3][4][5], On the other hand the enhanced liver metabolism follow ing oral estrogen administration may also be related to unwanted side effects like hyperten sion [6], venous thromboembolism [7][8][9] and gallbladder disease [8],…”
Section: Introductionmentioning
confidence: 99%
“…In order to further character ize the estrogenic effects of these 2 com pounds, the serum levels of the 2 estrogeninducible liver proteins pregnancy zone pro tein (PZP) [13] and sex-hormone-binding globulin (SHBG) [5,14] and of FSH were also recorded.…”
Section: Introductionmentioning
confidence: 99%